Políticas públicas de esporte e lazer: uma análise da gestão do município de Santarém - PA (2005 - 2012) - Rita Maria de Fátima Peloso Grasso (2015)
Public sport and leisure policies have been part of public agenda in Brazil since the 1930s, with leisure having legally been incorporated into the Federal Constitution as a social right since 1988. Particular emphasis has been set on the identification of problems concerning sport and leisure public policies in Brazil, particuly in terms of their historical constitution, social recognition and the cultural values envolved. The process of analyzing a public policy from a governmental management perspective requires an appreciation of institutional engineering, plus a good understanding of the distinguishing traits of the formulated and implemented programs, projects and actions. Above all, this involves discovering what governments actually make, with such public polícies being capable of influencing the lives of various social groups. The purpose of this study is to describe and analyze sport and leisure public policies in the municipality of Santarém, in Brazilian state of Pará between the 2005 and 2012 management period. The following aspects have been analysed in this particular contexto: sport, leisure and public policy concepts, the training of professional, the types of programs, projects and activities involved, the audiences, spaces and equipment for the development of these actions, and matters of financing. Qualitative research was performed through a combination of bibliographical, documentation and field research studies. The documents analyzed were: Reports and Planning of the Sport and Leisure Office (AEL), magazines with messages from the former mayor of the municipal Council, Annual Budget Laws, the Multi-annual Plan, and the Government change will advance Plan. The process used for the collection of data in the field was series of semi-structured interviews withn a total of 12 (twelve) managers, with the collected data then being analyzed using content analysis. It was discovered that limits are still in place in relation to the concept of sport, leisure and public policies, with the statements of some of the subjects and the contente of certain documenting a closeness between the principles that have delineated current policies. Even though management has not produced a training policy in itself, the actions out by profesionals to become suitably qualified. The sport and leisure programs, projects and other actions have been diversified, enabling contente to be expanded into this area. Activities performed by the Sport and Leisure Office (AEL) have attended to a target audience of various age groups but have not reached out to specific audiences such as the disabled, quilombola communities and indigenous peoples. There has also been na invrease in exercise areas and equipment throughout the city, affording increased access for the popution. Fially, the financing for the development of AEL, activities has since evolved and increased, albeit less than ideally, in relation to matters covered by research.